AN EFL TEACHER'S CODE SWITCHING IN A YOUNG LEARNERS' CLASS - Khaerunnisa, Lisa (2016)
The case of EFL teacher's code switching in EYL class in a multilingual country like Indonesia has sparked much interest of many researchers. However, recently, studies about EFL teacher's code switching in EYL class are dominated by the investigation of code switching in two languages only. Thus, in order to enrich the findings of EYL teacher's code switching which involves more than two languages in multilingual context, this study aims to investigate an EFL teacher's code switching which involves English, Indonesian, and Javanese in an EYL class. Specifically, this descriptive qualitative study aims to investigate the teacher's types of code switching, her reasons to do code switching, and effects of her code switching toward the students' competency accomplishment based on the arrangement in the teaching syllabus and lesson plan. There are four major findings found from classroom observations, teacher's interview, students' questionnaire, and students' interviews in this study. First, regarding the types of the teacher's code switching, she did conversational, inter-sentential, intra-sentential, and tag switching. Next, those types were used for six reasons including maximizing her role as a students' important knowledgeable partner, specifying the students based on their characteristics, presenting useful English exposure, delivering clear teaching materials, expressing clear emotions, and delivering jokes. Further, her code switching gave positive effects toward the students' competency accomplishments. Her code switching could ease the students to understand her teaching instructions and explanations. As a consequence, two indicators of students' competency accomplishment emerged in the teaching and learning process in ten meetings. Lastly, it could also bring negative effects. The overuse of Indonesian and Javanese in her code switching could reduce the amount of students' English exposure and continue their dependence on their teacher's use of those two languages. Therefore, it can be concluded that her code switching can only contribute to the effectiveness of her teaching to achieve the objectives of teaching and learning in particular meetings, but still cannot effectively provide proper target language input for the students and form their positive learning behavior. Based on the aforementioned findings, it is recommended that the teacher's code switching should not be dominated by the use of non-English languages in order to get its advantages and avoid its disadvantages. Keywords: Code switching, Teacher's talk, EFL teaching, EYL teaching Kasus alih kode yang dilakukan oleh guru EFL di kelas EYL di negara multilingual seperti Indonesia telah mencetuskan banyak ketertarikan para peneliti. Meskipun demikian, belakangan ini penelitian tentang alih kode yang dilakukan oleh guru EFL didominasi oleh investigasi mengenai proses alih kode yang hanya melibatkan dua bahasa. Maka dari itu, untuk memperkaya temuan tentang alih kode yang dilakukan oleh guru EYL yang melibatkan lebih dari dua bahasa dalam konteks multilingual, penelitian ini ditujukan untuk menyelidiki proses alih kode seorang guru EFL yang melibatkan Bahasa Inggris, Bahasa Indonesia, dan Bahasa Jawa di sebuah kelas siswa sekolah dasar. Secara khusus, penelitian deskriptif kualitatif ini bertujuan untuk meinginvestigasi tipe alih kode guru, alasanya untuk melakukan alih kode, dan efek dari alih kodenya terhadap pencapaian kompetensi siswa berdasarkan ketetapan dalam silabus dan rencana pelaksaan pembelajaran. Terdapat empat temuan utama yang ditemukan dari observasi kelas, wawancara guru, kuesioner siswa, dan wawancara siswa pada penelitian ini. Pertama, perihal tipe alih kode guru, tipe alih kodenya meliputi conversational, inter-sentential, intra-sentential, dan tag. Berikutnya, tipe-tipe tersebut digunakan oleh guru untuk enam alasan utama meliputi memaksimalkan perannya sebagai partner berpengetahuan yang penting bagi para siswanya, menspesifikan para siswanya sesuai karakter mereka, menghadirkan paparan Bahasa Inggris yang berguna, menyampaikan materi ajar yang jelas, mengekspresikan emosi yang jelas, dan menyampaikan lelucon dalam proses mengajar. Selanjutnya, alih kodenya memberikan efek positif pada pencapaian kompetensi siswa. Alih kodenya dapat memudahkan siswa untuk memahami instuksi dan penjelasan dari guru. Sebagai konsekwensinya, dua indikator pencapaian kompetensi siswa muncul di sepuluh pertemuan. Terakhir, proses alih kode guru juga dapat memberi efek negatif. Penggunaan Bahasa Indonesia dan Bahasa Jawa yang berlebihan dapat mengurangi jumlah paparan Bahasa Inggris bagi siswa dan meneruskan ketergantungan mereka terhadap penggunaan kedua bahasa tersebut oleh guru mereka. Maka dari itu, dapat disimpulkan bahwa penggunaan alih kode guru hanya dapat berkontribusi pada efektivitas pengajarannya dalam mencapai tujuan pembelajaran di pertemuan-pertemuan tertentu, akan tetapi belum dapat secara efektif menyediakan input bahasa target yang baik dan membentuk sikap belajar siswa yang positif. Berdasarkan temuan-temuan di atas, dapat direkomendasikan bahwa untuk mendapatkan manfaat dan menghindari kerugian dari penggunaan alih kode guru, proses alih kode guru seharusnya tidak didominasi oleh penggunaan bahasa selain Bahasa Inggris. Kata Kunci: Alih kode, Tutur guru, Pengajaran EFL, Pengajaran EYL